Effect of Environmental Accounting Disclosure, Environmental Performance, Company Size and Corporate Social Responsibility Disclosure - Koapaha, Hartiny Pop (STIE Amkop Makassar, 2024)
This study examines the effect of environmental accounting disclosure, environmental performance disclosure, company size and corporate social responsibility disclosure on firm value. The method in this study uses the SPPS 24 method by testing individually between the independent variables on the dependent variable and simultaneously. The population in this study took 90 mining companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The data collection technique used purpose sampling. The results obtained from this study are that simultaneously the environmental accounting disclosure variable, environmental accounting disclosure and company size and corporate social responsibility disclosure have a significant effect on Firm Value while individually, company size has no effect on Firm Value. Individually, the results show that Environmental Accounting Disclosure has an effect on Firm Value with a P-value of 0.036 at a significant level of 5%. Similarly, Environmental Performance Disclosure has a significant effect on Firm Value with a P-value of 0.037 at a significant level of 5%. And simultaneously independent variables have a significant effect on company value or by 16.8%. Company size variable has no effect with a p-value of 0.707 greater than 0.05% significant level